1995
DOI: 10.1515/pteridines.1995.6.4.173
|View full text |Cite
|
Sign up to set email alerts
|

6R-L-erythro-5,6,7,8-Tetrahydrobiopterin and Dopamine Release

Abstract: SummaryWe previously reported that intracerebroventricular administration of 6,7,, a cofactor for aromatic amino acid hydroxylases and nitric oxide synthase, induces an increase in DOPA levels (as an index of DA biosynthesis) and in levels of DA metabolites (as an index of DA release) in the rat brain: the increase in DOPA levels was larger than that of DA metabolites, indicating that 6R-BH 4 enhances DA release. In the present study, we examined the effects of 6R-BH 4 on DA release in vivo from the striatum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Following administration of BH 4 in vivo rat microdialysis studies have shown that (a) DA release was increased in the striatum with the release not dependent on the biosynthesis of DA [9,13] , and (b) the DA-releasing action was independent of the action of BH 4 as a cofactor for TH and NOS, and was mediated by a specifi c recognition site for BH 4 on DA neurons or related cells [14] . In addition, dialytic perfusion of BH 4 in rats was determined via microdialysis to increase the in vivo release of DA (in the striatum and frontal cortex), 5-HT (in the striatum), and glutamate (in striatum and frontal cortex) [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Following administration of BH 4 in vivo rat microdialysis studies have shown that (a) DA release was increased in the striatum with the release not dependent on the biosynthesis of DA [9,13] , and (b) the DA-releasing action was independent of the action of BH 4 as a cofactor for TH and NOS, and was mediated by a specifi c recognition site for BH 4 on DA neurons or related cells [14] . In addition, dialytic perfusion of BH 4 in rats was determined via microdialysis to increase the in vivo release of DA (in the striatum and frontal cortex), 5-HT (in the striatum), and glutamate (in striatum and frontal cortex) [10] .…”
Section: Introductionmentioning
confidence: 99%